Blended Learning Model (BLM) in English Pronunciation Class: Lesson from Indonesia - Yuliyanto Sabat; Suwarsih Madya; Basikin Basikin; Abd. Syakur (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Blended Learning Model (BLM) has frequently been viewed as one of the most effective models in teaching. Many studies have been conducted to reveal the effectiveness of BLM to teach various subjects, yet very few previous studies touched the use of BLM to teach English pronunciation. This research aimed at filling the gap describing how English pronunciation teacher put into practice the BLM in pronunciation instruction and what the students’ responses toward this model. This research used qualitative research method and employed field notes observation, a set of questionnaires, and semi-structured interview as the instruments. The research participants were 29 students from English education study program at teacher training institute at STKIP PGRI Sidoarjo, East java, Indonesia. The result showed that BLM was employed through three related stages in pronunciation class; online materials, the online tutor, and the face-to-face teacher. Additionally, BLM increased students’ interests and motivation to learn pronunciation. These results can be viewed as a source of perspective points while teaching pronunciation skill in EFL setting.